Upgrading exploitation axials’ pins qualities of mounted wheels through hard facing - Lubenska, L. M.; Kolodiazhnyi, P. V. (Science and Transport Progress, 2011)
The analysis of destruction causes of wheelset axles in service is performed. Reducing of depth of cavities of a rough surface is 3 times with a combination of the finish turning and vibration-formation processing. The effect of hardening the surface layer to a depth of 0.15 mm under the influence of vibration with frequency of 43 Hz and amplitude of 5·10 –3 m is exposed. The effect of reduction of microhardness of the hardened surface layer with increasing temperature and duration of exposure to vibration is detected.